1999
DOI: 10.1002/(sici)1098-2264(199907)25:3<195::aid-gcc1>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic changes defining the genesis, progression, and malignancy potential in solid human tumors: A phenotype/genotype correlation

Abstract: The transition of normal epithelium to invasive carcinoma occurs sequentially. In colorectal and cervical carcinogenesis, this transition is reflected by histomorphologically defined grades of increasing dysplasia that untreated may progress to invasive disease. In an attempt to understand the role of chromosomal aberrations during tumorigenesis we have applied comparative genomic hybridization using DNA extracted from defined stages of colorectal and cervical tumors, from low‐ and high‐grade astrocytic tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
188
1
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(210 citation statements)
references
References 27 publications
19
188
1
2
Order By: Relevance
“…IFISH has higher sensitivity than other methods used for this purpose, such as CGH, which detects copy number changes if they are present in more than 50% of the cell population (21). IFISH can identify CI in small subpopulations of interphase cells (68), allowing the detection of infrequent, possibly random changes before they lead to clonal expansion (20).…”
Section: Figure 2 P53 Ihc (Do7)mentioning
confidence: 99%
“…IFISH has higher sensitivity than other methods used for this purpose, such as CGH, which detects copy number changes if they are present in more than 50% of the cell population (21). IFISH can identify CI in small subpopulations of interphase cells (68), allowing the detection of infrequent, possibly random changes before they lead to clonal expansion (20).…”
Section: Figure 2 P53 Ihc (Do7)mentioning
confidence: 99%
“…One critical downstream target of this signaling pathway is the activation of protein-Ser/ Thr kinase (AKT)-1, which subsequently e ects multiple cellular processes, including increased cellular proliferation or decreased apoptosis, and contributes to tumorigenesis (Klippel et al, 1998;Kennedy et al, 1997;Tlsty, 1999). Because ampli®cation in 3q is also the most consistent chromosomal aberration found in cervical cancer, and is implicated in the progression of dysplastic uterine cervical cells into invasive cancer (for review, Rooney et al, 1999;Ried et al, 1999), the present study sought to determine the contribution of PIK3CA in cervical tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] CGH studies on both colorectal adenomas and carcinomas have also confirmed the gain of chromosome 7 material as a frequent change. 11,12,25,26 Ried et al 12 demonstrated gain of chromosome 7 material in 4 of 12 in what they described as high-grade adenomas. The neoplasia-specificity of ϩ7 has been questioned, however, both in the context of colorectal carcinogenesis and in general.…”
Section: Discussionmentioning
confidence: 99%
“…5-7,16 -18 Similar results have been obtained by CGH analyses of colorectal adenomas and carcinomas. 11,25,26 In adenomas, Ried et al 12 described gain of chromosome 13 material in 1 of 26 adenomas and gain of chromosome 20 material in 3 of 26 adenomas. All cases with these changes were described as high-grade adenomas.…”
Section: Discussionmentioning
confidence: 99%